Synchronization of estrus in yearling beef heiferswith the melengestrol Acetate®/prostaglandin F2"system: II. timed insemination - Larson, Robert L.; Corah, L.R.; Viker, S.V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Inseminating heifers 72 hr after the PG injection in the melengestrol acetate/ prostaglandin F (MGA®/PG) estrous synchronization system, without regard to behavioral estrus, tended to improve (P=.2) the percent of heifers pregnant to artificial insemination (AI) when compared to synchronized heifers bred 12 h after they were first detected in estrus. In the timed inseminated treatment, heifers exhibiting behavioral estrus 48 to 72 h after PG tended to have a higher (P<.12) conception rate to AI than heifers showing estrus within 48 h after PG. For situations in which the number of heifers conceiving to AI is more economically important than first service conception rate, or when labor restrictions make estrous detection impossible, timed insemination at 72 h after PG in the MGA/PG system shows promise as a management option.
Keywords: Beef; MGA/PG; Heifers; Timed mating; Conception rates